Genetic polymorphisms and cardiovascular outcomes in Chinese patients undergoing PCI and treated with clopidogrel and aspirin. (25th November 2020) - Xu, K; Ying, L; Chen, J; Xu, L; Li, J; Zhu, H; Wang, F; Yang, L; Zhang, J; Fan, Y; Zhu, T; Kong, D; et al.
Abstract: Background: Genetic polymorphisms of key proteins involved in clopidogrel absorption, metabolism, and action may contribute to variability in platelet inhibition in patients undergoing percutaneous coronary intervention (PCI), but their impacts on cardiovascular outcomes remain unclear. Purpose: To examine the associations between genetic polymorphisms and cardiovascular outcomes in Chinese patients undergoing PCI and treated with clopidogrel and aspirin. Methods: This prospective cohort study consecutively enrolled 2, 453 post-PCI patients treated with clopidogrel and aspirin. Adenosine diphosphate-induced platelet aggregation was measured by light transmission aggregometry. A total of 40 single nucleotide polymorphisms (SNPs) of 18 genes selected according to published studies were investigated using an improved multiplex ligation detection reaction technique. The primary outcome was major adverse cardiovascular event (MACE), the composite of cardiovascular death, non-fatal myocardial infarction (MI), and ischemic stroke within one year after PCI. Results: We restricted the analyses to the first 1, 452 patients who had finished one-year follow-up and complete data on genotyping and platelet aggregation. 44 (3.03%) patients suffered MACE. Among the 40 SNPs, only the A-allele carriers of CYP2C19*2 had a significant higher risk of MACE (adjusted HR 2.05; 95% CI, 1.01–4.19; p=0.048) and platelet aggregation than non-A-carriers after adjusting age, sex, MI presentation, and left ventricular ejection fraction. CYP2C19*3, CYP2B6 rs3745274, and PEAR1 rs12041331 variants were also significantly associated with platelet aggregation (all p<0.05) but not with MACE at 1 year. Conclusion: About 54.2% of Chinese patients with PCI were A-allele carriers of CYP2C19*2, who face a two-fold higher risk of MACE than non-A-allele carriers in Chinese patients after PCI. It would help identify low clopidogrel responders and optimize antiplatelet therapy before drug administration. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Funding of China